High strain tolerance gradient thermal barrier coating resistant to cmas corrosion and method of making

CN122979809APending Publication Date: 2026-10-27AECC COMML AIRCRAFT ENGINE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510544754.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

同时,熔融的CMAS还会导致热障涂层中的稳定成分溶解,诱发腐蚀导致涂层过早失效

Benefits of technology

[0003]本发明的目的在于提供一种耐CMAS腐蚀的高应变容限梯度热障涂层,提高热障涂层的热循环寿命。本发明还提供一种耐CMAS腐蚀的高应变容限梯度热障涂层的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979809A_ABST
    Figure CN122979809A_ABST
Patent Text Reader

Abstract

The application discloses a CMAS corrosion resistant high-strain tolerance gradient thermal barrier coating and a manufacturing method thereof, and belongs to the field of heat resistant coatings. The coating comprises a lower heat insulation layer, a transition layer and a DVC layer, the lower heat insulation layer is a yttria stabilized zirconia layer, the transition layer is a high-RE-content doped zirconia layer without cracks, and the DVC layer is a high-RE-content doped zirconia layer comprising through vertical cracks. The transition layer separates the vertical cracks in the DVC layer from the lower heat insulation layer, effectively prevents the DVC layer from peeling off due to the lateral expansion of the vertical crack tip after extending to the lower heat insulation layer rear interface, and improves the service life of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heat-resistant coatings, specifically relating to a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion and its manufacturing method. Background Technology

[0002] During high-temperature operation, gas turbines ingest pollutants such as dust, gravel, and volcanic ash, which form low-melting-point calcium magnesium aluminum silicate glassy phase deposits (CMAS). The melting temperature of CMAS is typically lower than the service temperature of the gas turbine. Molten CMAS can penetrate into cracks, pores, or columnar intergranular structures within the thermal barrier coating (TBC) on the surface of high-temperature components of the gas turbine, leading to a decrease in the TBC's thermal insulation performance and an increase in its elastic modulus, thus significantly reducing the coating's strain tolerance. Simultaneously, the molten CMAS can also cause the dissolution of stabilizing components in the TBC, inducing corrosion and causing premature coating failure. Some technical solutions improve resistance to CMAS corrosion by setting an interface layer with high rare earth element (RE) content on the surface of traditional YSZ coatings. However, since highly RE-doped coatings have relatively low fracture toughness, improved coating solutions further introduce dense vertically cracked (DVC) cracks into the highly RE-doped coating to improve the coating's strain tolerance. Under certain operating conditions, vertical crack tips can easily induce transverse cracks along the interface between the highly RE-doped coating and the YSZ coating, accelerating the peeling of the highly RE-doped coating. Therefore, providing a thermal barrier coating with longer service life and resistance to CMAS corrosion is of positive significance for improving the reliability and economy of gas turbines. Summary of the Invention

[0003] The purpose of this invention is to provide a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion, thereby improving the thermal cycling life of the thermal barrier coating. This invention also provides a method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion.

[0004] According to one aspect of the present invention, a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion is provided, the coating comprising a lower insulating layer, a transition layer, and a DVC layer, wherein:

[0005] The lower heat insulation layer is a yttrium oxide stabilized zirconium oxide layer;

[0006] The transition layer is a crack-free, highly RE-doped zirconium oxide layer;

[0007] The DVC layer is a highly RE-doped zirconium oxide layer including through-through vertical cracks.

[0008] The rare earth oxides in the highly RE-doped zirconium oxide account for 10%-60% by weight, and the rare earth oxides include SrO, Y2O3, La2O3, Ce2O3, and Pr6O.11 One or more combinations of Nd2O3, Sm2O3, Eu2O3, Gd2O3, and Yb2O3.

[0009] By setting a crack-free transition layer between the lower insulation layer and the DVC layer, the vertical crack tip can be effectively prevented from extending to the interface between the lower insulation layer and the DVC layer, thereby inhibiting the lateral propagation of cracks along the interface, thus preventing premature peeling of the CMAS corrosion-resistant DVC layer and improving the thermal barrier coating's thermal cycle life.

[0010] Furthermore, in some embodiments, the porosity of the lower insulation layer is 5% to 20%, the thickness is 0.1 mm to 1 mm, and there are no cracks in the lower insulation layer.

[0011] Furthermore, in some embodiments, the thickness of the transition layer accounts for 10%-50% of the CMAS corrosion-resistant high strain-tolerant gradient thermal barrier coating.

[0012] Furthermore, in some embodiments, the porosity of the transition layer is 5%-15%, and the thickness is 0.02-0.5 mm.

[0013] Furthermore, in some embodiments, the transition layer is configured as a 55YSZ layer.

[0014] Furthermore, in some embodiments, the lower insulation layer is configured as a 6-8YSZ coating.

[0015] Furthermore, in some embodiments, the vertical crack density in the DVC layer is >1 crack / mm, and the porosity is <10%.

[0016] Furthermore, in some embodiments, the bottom of the DVC layer includes a connecting layer, which has the same composition as the transition layer.

[0017] Furthermore, in some embodiments, the DVC layer includes multiple DVC gradient layers, and the multiple DVC gradient layers have different compositional compositions.

[0018] According to another aspect of the present invention, a method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion is provided, the method comprising the following steps:

[0019] Step a): Provide a high-temperature alloy substrate, and spray a yttrium oxide-stabilized zirconia layer onto the high-temperature alloy substrate to obtain the lower heat insulation layer;

[0020] Step b): Preheat the lower insulation layer at a first temperature, and spray a highly RE-doped zirconia layer onto the lower insulation layer at a first spraying distance to obtain a transition layer;

[0021] Step c): The transition layer is preheated at a second temperature, and then a highly RE-doped zirconia layer is sprayed on the transition layer at a second spraying distance while providing high-pressure air cooling to the spraying surface and back side of the high-temperature alloy substrate, to obtain a DVC layer including through longitudinal cracks.

[0022] Where the second temperature is greater than the first temperature.

[0023] The second spraying distance is less than the first spraying distance;

[0024] The rare earth oxides in the highly RE-doped zirconium oxide account for 10%-60% by weight, and the rare earth oxides include SrO, Y2O3, La2O3, Ce2O3, and Pr6O. 11 One or more combinations of Nd2O3, Sm2O3, Eu2O3, Gd2O3, and Yb2O3.

[0025] Furthermore, in some embodiments, step a) further includes the step of setting a NiCoCrAlY adhesive layer on the high-temperature alloy substrate before spraying the yttrium-stabilized zirconia layer.

[0026] Furthermore, in some embodiments, in step b), the first temperature is 80℃-200℃, the first spraying distance is 100mm-120mm, the spraying linear speed is 800mm / s-1200mm / s, and the spraying method includes atmospheric plasma spraying, plasma spraying-physical vapor deposition, or suspension plasma spraying.

[0027] Furthermore, in some embodiments, in step c), the second temperature is 250℃-500℃, the second spraying distance is 70mm-100mm, the spraying linear speed is 500mm / s-800mm / s, and the spraying method includes atmospheric plasma spraying, plasma spraying-physical vapor deposition, or suspension plasma spraying.

[0028] Furthermore, in some embodiments, the method is used to manufacture the high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion provided in any of the foregoing embodiments. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of a high strain-tolerant gradient thermal barrier coating structure resistant to CMAS corrosion in one embodiment.

[0030] Figure 2 Metallographic image of a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion in one embodiment.

[0031] Meaning of the reference numerals in the attached figures:

[0032] 1-Alloy substrate; 2-Metallic bonding layer; 3-Lower insulation layer; 4-Transition layer; 5-DVC layer; 6-Vertical crack.

[0033] The purpose of the above-described drawings is to provide a detailed description of the present invention so that those skilled in the art can understand the technical concept of the invention, and is not intended to limit the invention. For the sake of brevity, the above-described drawings only schematically depict the structures related to the technical features of the present invention, and do not depict the complete structure and all details strictly according to actual scale. Detailed Implementation

[0034] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings.

[0035] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment herein. The phrase appearing in various places in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive, independent, or alternative embodiments. Those skilled in the art will understand that the embodiments herein can be combined with other embodiments without structural conflict. In the description herein, "a plurality of" means at least two.

[0036] The service temperature of a gas turbine determines its efficiency; therefore, to further improve the economics of gas turbines, the design service temperature of advanced gas turbines is becoming increasingly higher. To extend the service life of hot-end components of gas turbines, thermal barrier coatings (TBCs) are commonly applied to the surfaces of components such as combustion chamber injectors, combustion chambers, and turbine blades. Among these, yttria-stabilized zirconia (YSZ) coatings have gained widespread application due to their low thermal conductivity, thermal expansion coefficient close to that of the metal substrate, and good chemical stability under high-temperature conditions.

[0037] However, during the service of a gas turbine, it inevitably ingests impurities such as dust, gravel, and volcanic ash. These impurities undergo complex reactions in the high-temperature gas and form low-melting-point calcium magnesium aluminum silicate glassy phase deposits (CMAS) on the surface of hot-end components. The melting point of CMAS is usually lower than the service temperature of the gas turbine. This means that when the gas turbine is operating, the molten CMAS can easily penetrate into the thermal barrier coating through cracks, pores, and columnar intergranular structures on the surface of the thermal barrier coating. This leads to a decrease in the porosity of the thermal barrier coating, a decrease in thermal insulation performance, an increase in the elastic modulus, and a significant reduction in the coating's strain tolerance. At the same time, the molten CMAS can rapidly dissolve the Y in the YSZ coating that plays a stabilizing role for tetragonal zirconia and precipitate Y-depleted zirconia. During the cooling process, the Y-depleted zirconia undergoes a martensitic phase transformation accompanied by a volume expansion of about 5%, which significantly increases the internal stress of the YSZ coating, resulting in a significant loss of the thermal barrier coating's lifespan and increasing the risk of premature failure.

[0038] To extend the lifespan of thermal barrier coatings (TBCs), some approaches employ a corrosion-resistant barrier layer highly doped with rare earth elements (REs) on the TBC surface. This dense, RE-doped barrier layer isolates the CMAS from the YSZ coating, mitigating corrosion. However, the fracture toughness of the highly RE-doped barrier layer is significantly lower than that of the conventional 6-8YSZ coating, leading to a decrease in the composite coating's strain tolerance and thermal cycling life. To overcome this drawback, a further improved composite coating incorporates dense vertically cracked (DVC) structures within the barrier layer. During thermal cycling, these vertical cracks absorb strain, thereby improving the composite coating's strain tolerance.

[0039] However, the dense vertical crack structure extends to the interface between the barrier layer and the YSZ coating. During thermal cycling, especially in the presence of CMAS, the crack tip is very likely to induce transverse cracks that propagate along the interface. The development of transverse cracks will cause the barrier layer to peel off and fail, causing the coating to lose its resistance to CMAS.

[0040] To overcome the above problems, one embodiment of the present invention provides a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion. The coating has a composite structure, its surface has good resistance to CMAS corrosion, and it is not easy to peel off during thermal cycling, which can effectively extend the service life of the thermal barrier coating.

[0041] The coating structure is as follows Figure 1 As shown, it includes a lower insulation layer 3, a transition layer 4, and a DVC layer 5.

[0042] The lower heat insulation layer 3 is attached to the alloy substrate 1 via a metal adhesive layer. The lower heat insulation layer 3 is a yttrium oxide-stabilized zirconium oxide layer with good heat insulation properties, which can protect the alloy substrate from high-temperature combustion gas corrosion. In a preferred embodiment, the lower heat insulation layer 3 is a 6-8YSZ coating.

[0043] DVC layer 5 is a highly RE-doped zirconia layer. The high RE doping amount gives it good resistance to CMAS corrosion. DVC layer 5 includes uniform and dense vertical cracks 6, with at least some of the vertical cracks 6 penetrating DVC layer 5. In a preferred embodiment, the density of vertical cracks 6 in DVC layer 5 is >1 crack / mm; DVC layer 5 has high density and porosity <10%. In different embodiments, the composition distribution of DVC layer 5 in terms of thickness can be uniform, or it can be set as a gradient layer with multiple different gradients, so that each gradient layer has a different composition. Specifically, different gradient layers can have different RE doping ratios or different RE doping elements.

[0044] A transition layer 4 is disposed between the lower thermal insulation layer 3 and the DVC layer 5. The transition layer 4 is a crack-free, highly RE-doped zirconia layer. The transition layer 4 improves the connection strength between the DVC layer 5 and the lower thermal insulation layer 3, and isolates the vertical crack 6 from the lower thermal insulation layer 3, preventing the tip of the vertical crack 6 from laterally propagating along the interface of the lower thermal insulation layer 3, thereby effectively reducing the risk of peeling off the DVC layer 5. In a preferred embodiment, the thickness of the transition layer 4 accounts for 10%-50% of the total thickness of the CMAS corrosion-resistant high strain-tolerant gradient thermal barrier coating (lower thermal insulation layer 3 + transition layer 4 + DVC layer 5), and its porosity is 5%-15%. In a preferred embodiment, to improve the bonding strength and microstructure uniformity between the transition layer 4 and the DVC layer 5, the bottom of the DVC layer 5 is a connecting layer, and the transition layer 4 and the connecting layer have the same composition. It is easy to understand that when the DVC layer 5 is uniformly composed, the composition of the DVC layer 5 and the transition layer 4 is the same, and the DVC layer 5 as a whole is considered a connecting layer.

[0045] In the embodiments, the highly RE-doped zirconium oxide is 10-60 wt% rare earth oxide-stabilized zirconium oxide, wherein the rare earth oxide can be SrO, Y2O3, La2O3, Ce2O3, Pr6O, etc. 11 One or more combinations of Nd2O3, Sm2O3, Eu2O3, Gd2O3, and Yb2O3.

[0046] According to another aspect of the present invention, a method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion is provided, the method comprising the following steps:

[0047] First, a metal bonding layer 2 is formed on the alloy substrate 1. In a preferred embodiment, the metal bonding layer 2 is a NiCoCrAlY bonding layer. A yttrium oxide stabilized zirconium oxide layer is sprayed onto the metal bonding layer 2 to obtain the lower heat insulation layer 3.

[0048] Next, the alloy substrate 1 is preheated at a first temperature, and a highly RE-doped zirconia layer is sprayed onto the lower heat insulation layer 3 at a first spraying distance to obtain a crack-free transition layer 4. In a preferred embodiment, the first temperature is controlled at 80℃-200℃, the first spraying distance is 100mm-120mm, and the spraying linear speed is 800mm / s-1200mm / s.

[0049] Finally, the alloy substrate 1 is preheated at a second temperature. Then, while providing high-pressure air cooling to both the spraying surface and the back surface of the alloy substrate 1, a highly RE-doped zirconia layer is sprayed onto the transition layer 4 at a second spraying distance, resulting in a DVC layer 5 including a through-thickness vertical crack 6. The second temperature is higher than the first temperature, and the second spraying distance is shorter than the first spraying distance. In a preferred embodiment, the first temperature is controlled between 250°C and 500°C, the second spraying distance is 70mm-100mm, and the spraying linear speed is 500mm / s-800mm / s.

[0050] In a preferred embodiment, the profile structure of the high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion is as follows: Figure 2 As shown in the figure. Among them, the alloy substrate 1 is GH3536 alloy, the metal bonding layer 2 is NiCoCrAlY bonding layer, the lower heat insulation layer 3 is 8YSZ coating, and the transition layer 4 and DVC layer 5 are both 55YSZ layers.

[0051] This composite coating is manufactured in the following manner:

[0052] A GH3536 alloy component is provided as the alloy substrate 1, wherein the GH3536 alloy component is a circular disc structure with a diameter of 25.4 mm and a thickness of 5 mm. The GH3536 alloy component is sandblasted with 80-mesh corundum, followed by ultrasonic cleaning with anhydrous ethanol and drying. A 100 μm thick metal bonding layer 2 of NiCoCrAlY coating is deposited on the surface of the GH3536 alloy component using atmospheric plasma spraying (APS).

[0053] Using a SinplexPro spray gun, commercial coating Metco 204NS powder with a particle size of 11μm-125μm was used as raw material. The spraying power was set to 35kW, and the alloy substrate 1 was preheated by a non-powder-feeding purging method at a preheating temperature of 150℃. The settings were Ar 55Nlpm-70Nlpm, H2 5Nlpm-8Nlpm, powder feed rate of 30g / min-60g / min, spraying distance of 100mm-120mm, and spraying linear speed of 1000mm / s-1200mm / s. An 8YSZ coating of about 300μm thickness was sprayed on the surface of the metal bonding layer 2 to obtain the lower heat insulation layer 3.

[0054] The alloy substrate 1 is preheated to 80℃-200℃. Metco 208 powder with a particle size of 11μm-106μm is used as raw material. The spraying power is set to 45kW, Ar 55Nlpm-70Nlpm, H2 5Nlpm-8Nlpm, powder feed rate 30g / min-60g / min, spraying distance 100mm-120mm, and spraying linear speed 800mm / s-1200mm / s. A 55YSZ coating with a thickness of about 50μm is sprayed on the surface of the lower heat insulation layer 3 to obtain a crack-free transition layer 4. The porosity of the transition layer 4 is 5%-15%.

[0055] The alloy substrate 1 is preheated to 400℃. Metco 208 powder with a particle size of 11μm-106μm is used as raw material. The spraying power is set to 58.5kW, Ar 55Nlpm-70Nlpm, H2 6Nlpm-12Nlpm, powder feed rate 30g / min-60g / min, spraying distance 70mm-100mm, and spraying linear speed 500mm / s-800mm / s. A 55YSZ coating with a thickness of about 100μm is sprayed on the surface of the transition layer 4. During the spraying process, high-pressure air cooling is provided from both the spraying surface and the back surface of the alloy substrate 1 to obtain a DVC layer 5 including vertical cracks 6. The porosity of the DVC layer 5 is about 5%, and the density of vertical cracks 6 is about 5 cracks / mm.

[0056] Depend on Figure 2 As can be seen, the vertical cracks 6 in DVC layer 5 all extend perpendicularly along the coating thickness direction, with no accompanying transverse cracks. Testing showed that the coating bonding strength reached 26 MPa.

[0057] A comparative coating excluding transition layer 4 was manufactured using the same materials and process parameters as in the above embodiments. After CMAS was applied to the surfaces of the embodiment coating and the comparative coating, respectively, a gas impact test was conducted at 1400°C. Compared with the comparative coating, the high strain-tolerant gradient coating with CMAS corrosion resistance provided in the embodiments showed an increase in lifetime of approximately 66.7%.

[0058] The purpose of the above embodiments is to provide a further detailed description of the present invention in conjunction with the accompanying drawings, so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the present invention, optimization or equivalent substitution of the technical features involved, as well as combination of implementation methods in different embodiments without causing structural and principle conflicts, all fall within the protection scope of the present invention.

Claims

1. A high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion, characterized in that, It includes a lower insulation layer, a transition layer, and a DVC layer; among which, The lower heat insulation layer is a yttrium oxide stabilized zirconium oxide layer; The transition layer is a crack-free, highly RE-doped zirconium oxide layer; The DVC layer is a highly RE-doped zirconium oxide layer including through-through vertical cracks; The rare earth oxides in the highly RE-doped zirconium oxide account for 10%-60% by weight, and the rare earth oxides include SrO, Y2O3, La2O3, Ce2O3, and Pr6O. 11 One or more combinations of Nd2O3, Sm2O3, Eu2O3, Gd2O3, and Yb2O3.

2. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 1, characterized in that, The lower insulation layer has a porosity of 5%-20% and a thickness of 0.1mm-1mm, and is free of cracks.

3. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 1, characterized in that, The thickness of the transition layer accounts for 10%-50% of the thickness of the high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion.

4. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 3, characterized in that, The porosity of the transition layer is 5%-15%, and the thickness is 0.02mm-0.5mm.

5. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to any one of claims 1 to 4, characterized in that, The transition layer is configured as a 55YSZ layer.

6. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to any one of claims 1 to 4, characterized in that, The lower insulation layer is configured with a 6-8YSZ coating.

7. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to any one of claims 1 to 4, characterized in that, The DVC layer has a vertical crack density of >1 crack / mm, a porosity of <10%, and a thickness of 0.1mm-1mm.

8. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 7, characterized in that, The DVC includes a connecting layer that is connected to the transition layer and has the same composition.

9. The high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 8, characterized in that, The DVC layer includes multiple DVC gradient layers, and the multiple DVC gradient layers have different compositions.

10. A method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion, characterized in that, Includes the following steps: Step a): Provide a high-temperature alloy substrate, and spray a yttrium oxide-stabilized zirconia layer onto the high-temperature alloy substrate to obtain the lower heat insulation layer; Step b): Preheat the lower insulation layer at a first temperature, and spray a highly RE-doped zirconia layer onto the lower insulation layer at a first spraying distance to obtain a transition layer; Step c): The transition layer is preheated at a second temperature, and then a highly RE-doped zirconia layer is sprayed on the transition layer at a second spraying distance while providing high-pressure air cooling to the spraying surface and back side of the high-temperature alloy substrate, to obtain a DVC layer including through longitudinal cracks. Where the second temperature is greater than the first temperature. The second spraying distance is less than the first spraying distance; The rare earth oxides in the highly RE-doped zirconium oxide account for 10%-60% by weight, and the rare earth oxides include SrO, Y2O3, La2O3, Ce2O3, and Pr6O. 11 One or more combinations of Nd2O3, Sm2O3, Eu2O3, Gd2O3, and Yb2O3.

11. The method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 10, characterized in that, In step a), before spraying the yttrium-stabilized zirconia layer, a NiCoCrAlY bonding layer is also formed on the high-temperature alloy substrate.

12. The method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 10, characterized in that, In step b), the first temperature is 80℃-200℃, the first spraying distance is 100mm-120mm, and the spraying linear speed is 800mm / s-1200mm / s; the spraying method includes atmospheric plasma spraying, plasma spraying-physical vapor deposition, or suspension plasma spraying.

13. The method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to claim 10, characterized in that, In step c), the second temperature is 250℃-500℃, the second spraying distance is 70mm-100mm, and the spraying linear speed is 500mm / s-800mm / s; the spraying method includes atmospheric plasma spraying, plasma spraying-physical vapor deposition, or suspension plasma spraying.

14. A method for manufacturing a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion according to any one of claims 10 to 13, characterized in that, Used to manufacture a high strain-tolerant gradient thermal barrier coating resistant to CMAS corrosion as described in any one of claims 1 to 9.